Реалізація алгоритмів штучного інтелекту для розробки комп’ютерних ігор в unreal engine - Кулішов, Є. А. (ХНУРЕ, 2024)
For the past decades, videogame industry has gained a massive influence over the globe, and it grows larger each passing year. One of the key elements in games, that captivates eyes of many gamers around the world, is artificial intelligence, the ever-evolving technology. It allows developers to create behavioral patterns for in-game characters, that dictates them how to act when meeting certain situations, markers, etc. And the more industry grows, more advancements on videogame AI will be made. This text’s purpose is the analysis and comparison of pros and cons of game engines, methods of creation of projects and its influence on AI, and difference in usage of in-game mechanics between AI and player.
Keywords: розробка комп’ютерних ігор; ideogame industry